Pelatihan Daring Robotika bagi Siswa dan Guru di Sekolah Menengah Atas Kristen Yahya Bandung - Ratnadewi; Muliady; Agus Prijono; Aan Darmawan Hankawidjaja; Christian Felix (Jurnal Pemberdayaan Masyarakat, 2023)
During the era of adapting to new habits after the Covid-19 pandemic, on-line learning needs to be done, considering the problem of the spread of Covid-19 in Indonesia. Learning to improve logical thinking skills and abstraction skills is needed by high school students. This can be done by providing online robotics training. so that teaching and learning activities are still carried out online, and there is also a need for knowledge about robotics for students and teachers at SMAK Yahya. The implementation of this activity will be carried out online and will be accompanied by selected instructors who have been tested for their abilities in robotics. The results of this service are expected that participants can practice on their own about robotics, can train logical thinking, and can improve abstraction skills. Based on the results of the questionnaire obtained, it can be concluded that there was an increase of 30%-40%. Students who initially had 0% of knowledge about VEX robot programming increased to 30%-40%, of course this is still not satisfactory, but is expected to be able to provide basic knowledge about VEX robots. Need further learning that is more in-depth, because the capacity of each student is different, and the provision of supporting devices is also inadequate.